Cyanophycean Algae from Eastern Uttar Pradesh, India - Mishra, P. K.; Mehrotra, R. K.; Shukla, Madhulika; Prakash, Jai; Mishra, Purnima (Ecoprint: An International Journal of Ecology, 2009)
In the present paper 10 Cyanophycean algae belonging 10 genera have been described from eastern U.P. The genera described are: Chroococcus, Microcystis, Aphanothece, Arthrospira, Spirulina, Lyngbya, Anabaena, Rivularia, and Gloeotrichia. All these forms are being reported for the first time from eastern U.P., India. doi: 10.3126/eco.v13i0.1627 Key words: Cyanophycean algae Ecoprint (An International Journal of Ecology) Vol. 13, No. 1, 2006 Page: 35-39